Vibrational Analysis of Building Structures with Irregularities - Colin Fox; Hyuck Chung (Applied Sciences)
This paper presents a mathematical model for predicting vibrations in lightweight, timber-based floor/ceiling structures, enhanced to account for irregularities in joist shape and stiffness, as well as floor stiffness. Building on a prior model that assumed precise geometry and homogeneous material properties, the study now incorporates real timber measurements via the power spectral density of irregularities to incorporate their impact on the system’s vibrational response, including mid-frequency vibrations. Existing results underscore the critical role of component connections in shaping vibration behavior, while the present paper gives new principles for building a model to assess how uncertainties in these connections or material properties affect the overall structural response. This new model maintains the property of efficient computation so that irregularities in the components may be included in the design stage to improve the mid-frequency performance of lightweight, timber-framed structures.